INOVASI BERBASISKAN CUSTOMER VALUE PADA VIDEO GAME VALORANT: STUDI KASUS - Verrnard Indranata Pontjoharyo (FEB Universitas Sam Ratulangi Manado, 2023)
Video games are becoming more and more popular, especially during the COVID-19 pandemic. Intense competition makes Game Developers think about the best concepts and ways to provide fun video games. Recently there was a Game Developer named Riot who developed a Game called Valorant. Surprisingly, Valorant became a successful and widely played game. As it turned out, Riot did not make major innovations, they only paid attention to the Customer Value and Customer Pain they had so far, and provided solutions for that. This study explores how Riot's process of making innovations that seem small but very impactful.